Simulation of high power deposition on target materials: applications in magnetic, inertial fusion, and high power plasma lithography devices - Hassanein, A. (Вопросы атомной науки и техники, 2006)
High power and particle deposition on target materials are encountered in many applications including magnetic and inertial fusion devices, nuclear and high energy physics applications, and laser and discharge produced plasma devices. Surface and structural damage to plasma-facing components due to the frequent loss of plasma confinement remains a serious problem for the Tokamak reactor concept. The deposited plasma energy causes significant surface erosion, possible structural failure, and frequent plasma contamination. The chamber walls in inertial fusion energy (IFE) reactors are also exposed to harsh conditions following each target implosion. Key issues include intense photon and ion deposition, wall thermal and hydrodynamic evolution, wall erosion and fatigue lifetime, and chamber clearing and evacuation to ensure desirable conditions prior to next target implosion. Both Laser and Discharge produced plasma are being used as a light source for extreme ultraviolet (EUV) lithography. A key challenge for Discharge Produced Plasma (DPP) and laser produced plasma (LPP) devices is achieving sufficient brightness to support the throughput requirements of High-Volume Manufacturing lithography exposure tools. An integrated model for the description of hydrodynamics and optical processes in a DPP device has been developed, integrated. And benchmarked.